2017
DOI: 10.3389/fphys.2017.00986
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Mathematical Models to Stem-Cell Derived Cardiomyocyte Lines Can Improve Predictions of Drug-Induced Changes to Their Electrophysiology

Abstract: Human induced pluripotent stem cell derived cardiomyocytes (iPSC-CMs) have applications in disease modeling, cell therapy, drug screening and personalized medicine. Computational models can be used to interpret experimental findings in iPSC-CMs, provide mechanistic insights, and translate these findings to adult cardiomyocyte (CM) electrophysiology. However, different cell lines display different expression of ion channels, pumps and receptors, and show differences in electrophysiology. In this exploratory stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
4
1

Relationship

6
4

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 78 publications
1
45
0
Order By: Relevance
“…Furthermore, such rapid characterisation using high-throughput systems can benefit precision and personalised medicine. For example, when using human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) in personalised medicine, as described in (26), characterisation of ion current kinetics may need to be taken into account, in order to tailor accurate cell line-specific models.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, such rapid characterisation using high-throughput systems can benefit precision and personalised medicine. For example, when using human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) in personalised medicine, as described in (26), characterisation of ion current kinetics may need to be taken into account, in order to tailor accurate cell line-specific models.…”
Section: Discussionmentioning
confidence: 99%
“…The Paci 2013 model is based on the data collected by Ma et al (20) using hiPSC-CMs. To address the variability between cells that is encountered in experiments, we identified G K1, critical for each I K1 formulation under investigation in a population of 22 cell-specific iPSC-CM models, published earlier by Lei et al (24). In brief, Lei et al (24) adapted the Paci 2013 model on the base of voltage clamp experiments carried out on hiPSC-CMs, by scaling the maximal conductance (S/F) of I Na (Â0.69), I CaL (Â0.80), I Ks , and the maximal activity of I NaCa (pA/pF) (tailored for each cell, the values are reported in Table 2).…”
Section: Comparing the Influence Of Cell-to-cell Variation Between Ipmentioning
confidence: 99%
“…However, if the majority of the variability is due to experimental artefacts, then a single set of kinetic parameters could accurately describe the physiology of each current type. If our findings also apply to myocytes, the standard approach to building action potential models with a single set of kinetic parameters for each current is appropriate Ten Tusscher et al Groenendaal et al (2015); Lei et al (2017), and the observed cell-cell variability in kinetics data is not required to be propagated forward in action potential simulations (as some studies have examined Pathmanathan et al (2015)). Nevertheless, we may still need an approach like the one demonstrated here to determine unbiased ion channel kinetic parameters to build the most physiologically-relevant action potential models; as opposed to taking the mean of biased recordings which could accidentally include some experimental artefacts within the kinetics models.…”
Section: Discussionmentioning
confidence: 99%